Investigación de índices eritrocitarios para determinación de anemia ferropénica, en niños de 1 a 10 años de edad, que acuden a la Clínica Guayaquil s.a del cantón Quevedo, provincia de los ríos, en el periodo de enero a junio del 2011 - Vidal Vera, Clara Mayra (2011)
Anemia is a finding of frequent laboratory in the infancy that affects the 20 % of the children in the developed countries. The hypoferric anemia is her more common, affecting 3 % of sucklings and to 2 % of adolescent women. The majority of the anemic children are without symptoms The main factors that contribute to anemia are the deposits of iron when being born, the quantity of iron in the diet, the frequency of infection and the little boy's genetic background. From the point of view fisiopatológico, anemia originates for three mechanisms: Enlarged destruction red corpuscles, blood losses and underproduction. ......